2017
DOI: 10.1186/s12891-017-1515-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bending speed on the lumbo-pelvic kinematics and movement pattern during forward bending in people with and without low back pain

Abstract: BackgroundImpaired lumbo-pelvic movement in people with low back pain during bending task has been reported previously. However, the regional mobility and the pattern of the lumbo-pelvic movement were found to vary across studies. The inconsistency of the findings may partly be related to variations in the speed at which the task was executed. This study examined the effects of bending speeds on the kinematics and the coordination lumbo-pelvic movement during forward bending, and to compare the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…Another possible explanation for our findings is that physical inactivity leads to deconditioning, and there is a strong association between reduced muscular function and the development of low‐back pain in pregnancy . Moreover, people with low‐back pain present deficits of the hip musculature, which provokes compensatory lumbopelvic movements, slowly movements and an increase of deconditioning, as well as pain . For that reason, it is possible that pregnant women with greater speed‐agility may suffer lower sciatic pain, or that those with sciatic pain may be more careful to reduce pain sensitivity through slower movements.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another possible explanation for our findings is that physical inactivity leads to deconditioning, and there is a strong association between reduced muscular function and the development of low‐back pain in pregnancy . Moreover, people with low‐back pain present deficits of the hip musculature, which provokes compensatory lumbopelvic movements, slowly movements and an increase of deconditioning, as well as pain . For that reason, it is possible that pregnant women with greater speed‐agility may suffer lower sciatic pain, or that those with sciatic pain may be more careful to reduce pain sensitivity through slower movements.…”
Section: Discussionmentioning
confidence: 93%
“…36 Moreover, people with low-back pain present deficits of the hip musculature, which provokes compensatory lumbopelvic movements, slowly movements and an increase of deconditioning, as well as pain. 37 For that reason, it is possible that pregnant women with greater speed-agility may suffer lower sciatic pain, or that those with sciatic pain may be more careful to reduce pain sensitivity through slower movements. Finally, our results show that better flexibility is associated with a reduction in bodily and sciatic pain in late pregnancy, which is consistent with the results found by Soriano-Maldonado et al 14 Nonetheless, the association between flexibility and pain outcomes in early pregnancy is still unclear and need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…As most back pain has come to be regarded as mechanical and related to function, back motion studies have been central in the search for functional biomarkers [5][6][7][8][9]. Here, intervertebral motion data provide more intrinsic information than surface studies and data from fluoroscopic sequences have been found to differentiate groups of patients with chronic nonspecific low back pain (CNSLBP) from healthy controls by virtue of the patterns of segmental motion [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tsang et al reported that bending speed imposes different levels of demand on the kinematics and pattern of the lumbo-pelvic movement and requires the ability to regulate the lumbo-pelvic movement pattern during forward bending while standing and demonstrated in pain free individuals. 9 Therefore, in the present study, bending speed was controlled by limiting execution to 5 seconds during forward bending by using a metronome. Kim et al reported that the lumbopelvic rhythm differed according to the low back pain subtypes, and the flexion angle of the lumbar spine was greater in the group with lumbar flexion with rotation syndrome associated low back pain than in the control group and the group with lumbar extension rotation syndrome associated low back pain; the hip flexion angle was greater in the lumbar extension rotation syndrome associated low back pain subgroup than in the control and lumbar flexion rotation syndrome group.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have reported an association between frequent forward bending and low back pain. [4][5][6][7][8][9][10] An activity or occupation that requires repetitive forward bending may be associated with herniated intervertebral discs in the lumbar spine. 11 The individual complains of flexion-related symptoms during forward bending.…”
Section: Introductionmentioning
confidence: 99%